Allergen management in the food industry - Boye, Joyce I.; Godefroy, Samuel Benrejeb (John Wiley & Sons, 2010)
"This book comprehensively addresses the sources of allergenic contaminants in foods, their fate during processing, and the specific measures that need to be taken to minimize their occurrence in foods"--Provided by publisher